2013
DOI: 10.1111/all.12154
|View full text |Cite
|
Sign up to set email alerts
|

Early skin testing is effective for diagnosis of hypersensitivity reactions occurring during anesthesia

Abstract: Allergic skin tests have to be performed 4-6 weeks after an allergic anesthetic reaction. Patients with allergic reactions during anesthesia were prospectively included (n = 44). Skin tests were performed in two stages: (i) Stage 1 (S1), 0-4 days after the reaction; and (ii) Stage 2 (S2), 4-8 weeks after. Five (11.5%) surgical procedures were suspended due to the reaction. Positive skin tests were obtained in 25/44 patients (57%). Allergic diagnosis was carried out at S1 in 15/25 (60%) and at S2 in 10/25 (40%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 9 publications
1
21
0
1
Order By: Relevance
“…This likely helped us to find a higher rate of positive skin tests, since previously published data report a decline over time in IgE antibodies in patients with drug allergy. 6,9,10,16,17 In 2013 Lafuente et al, found 25 patients (57%) with positive skin testing when performed at 0–4 days (Stage 1) and again at 4–8 weeks (Stage 2) after perioperative HSR. 17 Interestingly, a higher rate of skin test positivity was found in the Stage 1 (60%) compared to Stage 2 (40%) with three patients having positive skin testing only in Stage 1.…”
Section: Discussionmentioning
confidence: 99%
“…This likely helped us to find a higher rate of positive skin tests, since previously published data report a decline over time in IgE antibodies in patients with drug allergy. 6,9,10,16,17 In 2013 Lafuente et al, found 25 patients (57%) with positive skin testing when performed at 0–4 days (Stage 1) and again at 4–8 weeks (Stage 2) after perioperative HSR. 17 Interestingly, a higher rate of skin test positivity was found in the Stage 1 (60%) compared to Stage 2 (40%) with three patients having positive skin testing only in Stage 1.…”
Section: Discussionmentioning
confidence: 99%
“…The guidelines concur that triggers should be confirmed by re-taking the history of the anaphylactic episode and using this as a guide to selection of allergens for skin prick tests, measurement of allergen-specific IgE levels in serum, and additional investigations as needed [2-4,13-15,22,53,99-106]. Intradermal tests are helpful in investigation of anaphylaxis induced by insect venoms or drugs such as beta-lactam antibiotics [103-106].…”
Section: Comparative Review Of Collaborating Organizations’ Principalmentioning
confidence: 99%
“…Intradermal tests are helpful in investigation of anaphylaxis induced by insect venoms or drugs such as beta-lactam antibiotics [103-106]. Negative skin tests and absent or undetectable allergen-specific IgE levels have a high negative predictive value; however, positive tests have a lower positive predictive value because allergen sensitization without symptoms is widespread in the general population.…”
Section: Comparative Review Of Collaborating Organizations’ Principalmentioning
confidence: 99%
See 1 more Smart Citation
“…The odds ratio of obtaining a false-negative test 0-4 days after the reaction was 3.3 versus later testing (p = 0.09). The investigators noted that while early testing can be useful in some patients, it does not replace later testing [77]. …”
Section: Long-term Management: Prevention Of Recurrencementioning
confidence: 99%